Environmental Factors Related to Acute Rheumatic Fever and Rheumatic Heart Disease in Aceh Province - Herlina Dimiati; Sofia Sofia; Gani B (Budapest International Research and Critics University, 2020)
Acute rheumatic fever (ARF) is the body’s immune system reacting to an untreated infection with Group A Streptococcus (GAS) that affects skin, joints, brain, and heart. The heart damage that remains after an occurrence of ARF is called rheumatic heart disease (RHD). The objective of this study was to evaluate the ARF and RHD based on the profile of clinical diagnoses and emerging factors. The data were collected through interviews of the subjects, complete blood counts, the anti-streptolysin titer O analysis, the C-reactive protein Assay, and a statistical analysis. This research was a combination of clinical assessments, the CRP kit, anti-titer O kit, and interviews. The data were analyzed by employing Wilcoxon, Chi-square and Friedman test and also included a correlation analyzed using Spearman’s correlation with significance of (p<0.05. There were 63 samples of ARF and RHD patients involved, consisting of male (50.8%:32) and female (49.9%:31) patients (p<0.05). The factors that triggered ARF and RHD (p<0.05; r=0.88) as well as laboratory diagnosis (p<0.05) of these infections were measured. The ARF caused by residence also caused RHD by the interaction of time with the environment (p<0.05). The population consisted of males (32:50.8%) and females (31:49.2%), and it was not significant (p>0.05), while the streptococcal infection of RHD (63.5%) was much larger than in ARF (36.5%). This was based on the clinical diagnosis of RHD and ARF with a significance of (p<0.05). Also, the residence and the period of interaction with the environment were influences on the RHD and ARF.